Menggunakan Model Discovery Learning Untuk Meningkatkan Hasil Belajar Geografi Di Sma Negeri 1 Loghia Di Muna - Hasmin Hasmin; Ramli Ramli (Universitas Negeri Makassar, 2019)
SMAN 1 Loghia is one of school at Regency Muna who becomes researcher research object because the learning outcomes are still low, This is because only 40% meet the KKM. The purpose of this research: (1) To know student studying activities at SMA Country 1 Loghia who is taught by applying model discovery Learning; (2) To know activity teach teachers at SMA Country 1 Loghia who is taught by applying model discovery Learning; (3) To know result step-up study students at SMA Country 1 Loghia who is taught by applying model discovery Learning. The data in this research an quantitative and qualitative data which obtained from observation sheets and learning test result. Acquired observational result that by applying model discovery Learning: (1) activity study student increase with score average 3,2 get categories well; (2) activity teach to learn increase by scores average 3,6 get categories well; (3) result study student geography braze x IIS3 SMAN 1 Loghia increases from an average score of 60 to an average score of 80, with learned thoroughness 84% which is ≥ 75 according to the criteria for completing teaching determined by the school.SMAN 1 Loghia adalah salah satu sekolah di Kabupaten Muna yang menjadi objek penelitian peneliti karena hasil belajarnya yang masih rendah, hal ini dikarenakan hanya 40% yang memenuhi KKM. Tujuan penelitian:(1) Untuk mengetahui aktivitas belajar siswa di SMA Negeri 1 Loghia yang diajar dengan menerapkan model Discovery Learning (2) Untuk mengetahui aktivitas mengajar guru di SMA Negeri 1 Loghia yang diajar dengan menerapkan model Discovery Learning (3) Untuk mengetahui peningkatan hasil belajar siswa di SMA Negeri 1 Loghia yang diajar dengan menerapkan model Discovery Learning. Data dalam penelitian adalah data kualitatif dan kuantitatif yang diperoleh dari lembar observasi dan tes hasil belajar. Hasil penelitian diperoleh bahwa dengan menerapkan model Discovery Learning: (1) aktivitas belajar siswa meningkat dengan skor rata-rata 3,2 berkategori baik. (2) aktivitas mengajar guru meningkat dengan skor rata-rata 3,6 berkategori baik. (3) hasil belajar geografi siswa Kelas X IIS3 SMAN 1 Loghia meningkat dari rata-rata skor 60 menjadi rata-rata skor 80, dengan ketuntasan belajar 84% yang ≥ 75 sesuai dengan KKM yang ditentukan sekolah.